2006
DOI: 10.2109/jcersj.114.303
|View full text |Cite
|
Sign up to set email alerts
|

Proton Conductivity of Mesoporous Silica Incorporated with Phosphorus under High Water Vapor Pressures up to 150.DEG.C.

Abstract: 150c CȍǶǽ‫ڢ‬ᕮ⋛ᕧոˁǺǙǠȚɲɻ⓹۰ɩɅএઃȿɲȳǽɟɵɐɻଣҽමʸቆᇏ۠ɿʅறᗱʶȖଉ ɿৃቧ⚼ᅖଉ ɿૈ୮ ‫‬ ኇ̸গકӞᴻᲇકཪ⒈ᮾ᳣Ƀɻɇʀࢫ153-8904 ኇ̸ȩᬶ࠭ٚ‫ش‬ई 4-6-1 ଉ ኇ̸ᥴᲇগકకકȤకᏡ‫ك‬કᲇࢫ162-8601 ኇ̸ȩᄽٚᏱ 1-3Silica mesoporous structures incorporated with phosphorus were prepared and their proton conductivity was evaluated at temperatures of up to 150c C under saturated or controlled water vapor pressure. The fixing of phosphoric acid through heat treatment after forming the mesostructure had a limited effect on the improvement in proton conductivity only in a relatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
0
11
0
1
Order By: Relevance
“…Mesoporous silica containing phosphonate functional groups showed a conductivity of around 10 −2 S cm −1 at 100–120 °C and 100 % relative humidity, which is higher than that pristine mesoporous silica (ca. 10 −4 S cm −1 ) 77. Another mesoporous silica, Si‐MCM‐41, having sulfonate groups on the surface of the pores showed a conductivity of 0.2 S cm −1 at room temperature and 100 % relative humidity, which is considerably higher than the 10 −6 S cm −1 observed for pristine Si‐MCM‐41 78…”
Section: Proton Conduction In Mofsmentioning
confidence: 89%
“…Mesoporous silica containing phosphonate functional groups showed a conductivity of around 10 −2 S cm −1 at 100–120 °C and 100 % relative humidity, which is higher than that pristine mesoporous silica (ca. 10 −4 S cm −1 ) 77. Another mesoporous silica, Si‐MCM‐41, having sulfonate groups on the surface of the pores showed a conductivity of 0.2 S cm −1 at room temperature and 100 % relative humidity, which is considerably higher than the 10 −6 S cm −1 observed for pristine Si‐MCM‐41 78…”
Section: Proton Conduction In Mofsmentioning
confidence: 89%
“…The fast-growing diverse field of proton-conducting metal-organic frameworks (MOFs) is currently explored for promising applications as proton-exchange membranes, which is one of the key components in fuel-cell technology. [1][2][3] Nafion and Nafion-like polymer membranes are efficient proton conductors, [4,5] however the high costs and temperature limitations have driven a number of strategies towards the design of alternative materials, such as mesoporous silica, [6] coordination polymers (CPs), [1,7] and porous organic solids. [8] The first study of proton conduction in a 2D copper-and dithioxamide-based CP was reported in 1979 by Kanda et al [9] Kitagawa et al [10] extended this work by using derivatives of dithioxamides as organic linkers and reported the first systematic study on proton conduction in CPs.…”
mentioning
confidence: 99%
“…This indicates that nanogranular SiO 2 solid electrolyte fabricated at room temperature by PECVD method features the micro pore structure, which is desirable for proton conduction. 11,12 The important advantages of this micro pore structure include that it can provide a larger specific surface area and that it can be capable of adsorbing many water molecules, which will take place capillary condensation effect in the micro pores, 13 even make it like a pondlet. 14,15 The measured serial capacitance and phase angle as a function of the frequency of the applied voltage (0.2 V) for a capacitor based on nanogranular SiO 2 solid electrolyte are shown in Figure 2.…”
Section: Resultsmentioning
confidence: 99%